2009
DOI: 10.1074/jbc.m806559200
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Morphologically Distinct Oligomeric Forms of α-Synuclein

Abstract: Neuropathologic and genetics studies as well as transgenic animal models have provided strong evidence linking misfolding and aggregation of ␣-synuclein to the progression of Parkinson disease (PD) and other related disorders. A growing body of evidence implicates various oligomeric forms of ␣-synuclein as the toxic species responsible for neurodegeneration and neuronal cell death. Although numerous different oligomeric forms of ␣-synuclein have been identified in vitro, it is not known which forms are involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(130 citation statements)
references
References 65 publications
3
127
0
Order By: Relevance
“…Methods to detect morphologically distinct oligomeric forms of AS have been described [413]. Elevated levels of soluble AS oligomers were found in post-mortem extracts of PD [414] and DLB brains [415,416].…”
Section: α-Synuclein and Neurodegenerationmentioning
confidence: 99%
“…Methods to detect morphologically distinct oligomeric forms of AS have been described [413]. Elevated levels of soluble AS oligomers were found in post-mortem extracts of PD [414] and DLB brains [415,416].…”
Section: α-Synuclein and Neurodegenerationmentioning
confidence: 99%
“…This intrabody decreased the toxicity and aggregation of α-Syn in vitro [80]. Another intrabody, 10H, recognized a later-stage oligomer and inhibited toxicity induced by extracellular α-Syn, and also inhibited in vitro aggregation of α-Syn [81]. Recently Guilliams et al [82] reported additional anti-α-Syn nanobody, NbSyn87, obtained by immunization of llama with α-Syn.…”
Section: Intrabodies Targeted To Conformational α-Syn Epitopesmentioning
confidence: 99%
“…Addition of the acidic PEST peptide to four anti-α-Syn intrabodies improved the solubility for all 4, while still retaining sufficient intracellular levels of intrabody-PEST protein. In addition, the highest affinity, but least soluble of the parent constructs, the NAC-specific [81] Human scFv Oligomeric α-Syn Tomlinson I and J antibody library D10 [76] Human scFv Pan-specific Human scFv phage Griffin I library VH14 [74] Human nanobody Part of hydrophobic NAC of α-Syn Human nonimmune yeast surface display library NAC32 [74] Human scFv Part of hydrophobic NAC of α-Syn Human nonimmune yeast surface display library 6E [28] Human scFv Fibrillar α-Syn Tomlinson I and J antibody library NbSyn2 [79] Camelid VHH Monomeric α-Syn Phage display ScFv = single chain Fv; VHH = small heavy-chain-only antibody fragments; NAC = nonamyloid component human heavy-chain only nanobody, VH14, acquired the capacity to degrade α-Syn~GFP [90]. Thus, this bifunctional approach to the intrabody engineering can be used successfully to target and direct the molecule of choice to the required compartment, and shows great promise of targeting the earliest stages of neurodegeneration.…”
Section: Synmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have implicated small soluble oligomeric and protofibrillar forms of αS as the most neurotoxic species. [9][10][11][12] The influence of nanoparticles (NPs) on amyloid formation is of great interest due to their small sizes and high surface area-to-volume ratios. The small size of NPs allows them to access almost all parts of the human body; they even pass through the blood-brain barrier (BBB), which is the homeostatic defense mechanism of the brain.…”
Section: Introductionmentioning
confidence: 99%